Peran Komunikasi Rasional dalam Keberhasilan Pendampingan Pemberdayaan Masyarakat Adat Papua - Obeth Kaigere; Antik Tri Susanti; Elly Esra Kudubun (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Papua is an island at the eastern tip of Indonesia which is famous for its abundant natural wealth, but its people are still in poverty. The problem is focused on community empowerment. The purpose of this study was to describe the community empowerment program carried out by the Department of Livestock and Animal Health (Diskeswan) of Mimika Regency, Papua Province. In order to approach this problem, Habermas's reference to the theory of communicative rationality is used: objective communication, subjective and intersubjective communication. The type of research used in this research is descriptive, using qualitative research methods. Data collection techniques were carried out by observation, interviews, and documentation. The results of this study indicate that the communicative rationality of Habermas: objective communication, subjective and intersubjective communication, is successful in mentoring. Pig farmers are experiencing a change in managing pigs from the traditional way to a better way of rearing. The rationality of Habermas' communication in this study has proven to play a role in achieving the success of the assistance of the Papuan Indigenous People's pigs.